Penerapan Manajemen Risiko Teknologi Informasi Pada Perusahaan PT. X - Christian Natanael Sugiharto; Alexander Setiawan; Silvia Rostianingsih (Jurnal Infra, 2022)
Risk Management is one of the most crucial activities in today's business world. Along with the development of an increasingly complex era, making business people have to face many increasingly complex challenges as well. You can say that risk management must be implemented in companies that currently use IT in their dominant business processes in order to minimize risks and identify risks that will arise. The method used in this study to be applied to the company PT. X is COBIT 5 with two process domains, namely DSS01 Manage Operations and APO12 Manage Risk. The results of this study are some 24 (twenty four) company risks and risk mitigation related to what must be done in overcoming these risks.